Peningkatan Hasil Belajar IPA Materi Metamorfosis Melalui Model Jigsaw dan Project-Based Learning (PJBL) Berbantuan Media Pop-Up di Kelas III SDN Burneh 1 - Nadhira Febrianti Chandra; Rania Marsita Bela; Abdi Dwi Andika Putra; Conny Dian Sumadi (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
The low learning outcomes of science on the concept of metamorphosis in grade III of elementary school often stem from the limited use of concrete media and the dominance of verbal methods that are not in accordance with the stage of students' cognitive development. This study aims to examine the improvement of learning outcomes of metamorphosis materials through the gradual implementation of the Jigsaw model in Cycle I and Project-Based Learning (PjBL) assisted by pop-up media in Cycle II. The design used is a two-cycle Classroom Action Research (PTK) with 26 subjects of grade III students of SDN Burneh 1. Data collection was carried out through learning outcome tests, structured observation sheets, and documentation, then analyzed quantitatively descriptively using average scores and percentage of classical completeness. The success indicator is set at a classical completeness of at least 75%. The results of Cycle I showed an average class of 72.36 with a completeness of 69.23% (18 out of 26 students), not meeting the target. After reflection and switching to PjBL with pop-up media in Cycle II, the class average increased to 83.29 and classical completeness reached 84.62% (22 out of 26 students). In addition to cognitive improvement, there are noticeable improvements in aspects of collaboration, confidence, and depth of understanding of students' concepts. These findings indicate that a progressive combination of cooperative and project-based learning models supported by three-dimensional visual media is an effective strategy for learning abstract biology concepts in elementary school.